2014
DOI: 10.1136/jech-2014-204345
|View full text |Cite
|
Sign up to set email alerts
|

Raised levels of immunoglobulin G, A and M are associated with an increased risk of total and cause-specific mortality: the Vietnam Experience Study

Abstract: In the present study, high levels of Ig are associated with an elevated risk of death from total and 'other' causes, mainly infectious disease. High levels of Ig, particularly IgG, may signal subclinical disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…This makes it plausible that in older adults, both low sIgA and high serum IgA can be related to increased mortality. Some recent studies have shown higher serum IgA values associated with increased mortality risk [ 20 , 41 , 43 ]. However, in these cases the authors conclude that this is likely to be due to reverse causation whereby extant disease is responsible for elevated IgA levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it plausible that in older adults, both low sIgA and high serum IgA can be related to increased mortality. Some recent studies have shown higher serum IgA values associated with increased mortality risk [ 20 , 41 , 43 ]. However, in these cases the authors conclude that this is likely to be due to reverse causation whereby extant disease is responsible for elevated IgA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Certain types of kidney disease are also associated with abnormalities of the IgA system [ 19 ]. Recently, in a large study of Vietnam-era war veterans, we have found that higher levels of serum immunoglobulins, including IgA, were associated with around a two-fold increased risk of mortality from all-causes and ‘other’ causes (corresponding to deaths that were not ascribed to cardiovascular disease and cancer causes, largely comprising infectious diseases) [ 20 ]. On the other hand, severe serum IgA insufficiency which is inherited by up to 0.5% of the general population is also associated with higher mortality in the first 10–15 years from diagnosis in a Swedish population study [ 21 ] and has also been related to higher prevalence of coeliac disease, type I diabetes and other autoimmune diseases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of IgG are associated with an elevated risk of death from all-cause mortality, but most importantly from infectious disease. 46 In addition, some auto-antibodies such as anti-GM-CSF 47 and anti-IFN-γ have been associated with CM in otherwise immunocompetent patients. 48 Hence, in addition to total IgG, it may also be useful to follow auto-antibodies specific for inflammatory cytokines during infection.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Several diseases can be diagnosed through the assessment of immunoglobulin levels in biofluids. [29][30][31] Unfortunately, the current state-of-the-art immunoglobulin assays are lengthy and complicated. Here, pooled plasma further characterized the clinical potential of VAIA (Figure 3C).…”
Section: Zuschriftenmentioning
confidence: 99%